Monseñor Romero en el contexto de la Era Wojtyla (La Universidad, 2021)
The present work constitutes a reflection on the role of Karol Wojtíja in his capacity as Supreme Pontiff of the Catholic Church. The past ís analyzed in Poland, his native land, but only to clarify his aversion towards totalitarian regimes (Nazism and Stalinist communism). He also reviews the conflict he had with líberation theologians, with special emphasis on Latin America, and the distrust he showed for the way in which Monsignor Romero led the Salvadoran Church. But, on the other hand, part is also pointed out its position agaínst global capitalism, which he described as "wild" and materialist, as well as his position on the Iraq conflict, which he disapproved.